The Legal Politics of Regulating Special Terrorism Crimes under Law No. 1 of 2023 on the Criminal Code: Politik Hukum Pengaturan Tindak Pidana Terorisme Khusus dalam UU No. 1 Tahun 2023 tentang KUHP - Dede Indraswara; Cahya Wulandari; Muhammad Azil Maskur; Aisyah Nur Rafidah (Indonesian Journal of Counter Terrorism and National Security, 2025)
Legal politics in the context of criminal law must be analyzed seriously, both in relation to material criminal law and formal criminal law. Law No. 5 of 2018 concerning Terrorism Crimes and Law No. 9 of 2013 concerning Terrorism Financing Crimes underwent changes after the enactment of Law No. 1 of 2023 concerning the Criminal Code (Indonesian Criminal Code). This amendment includes a bridge article relating to criminal acts of terrorism within the Criminal Code, which thus has implications for the elaboration of general and special rules. The purpose of this research is to find out how to use logical (Logische Specialiteit) or systematic (Systematische Specialiteit) specialties in interpreting this matter. The method used is juridical-normative with an analytical and conceptual approach based on various legal literature. This research obtained 2 (two) results, namely an explanation of the rules against terrorism in Indonesian positive law and an explanation of the bridging article in the reform of the Indonesian Criminal Code with logical specificity. So it is concluded that the regulation of special terrorism regulations in the Criminal Code does not mean that it weakens the Special Law, but instead strengthens these special regulations in the future if there is a criminal act of terrorism.